Marketing Communication Strategies to Influence Brand Image - Chaiyasat, Seping (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The purpose of this research was to (1) Examine the strategies of marketing communication and product management of Hermes (2) To apply Hermes Marketing communication strategy to create a Thai brand image for leather industries. Data was collected by two methods which were qualitative method, using in department interviews from 25 interviewees and quantitative methods by using survey questionnaires. The data gathered from 128 Hermes potential clients to analysis the strategies of marketing communication and product management of Hermes. The data was analyzed randomly by snowball sampling. Research tools were the questionnaires which had been checked validated from experts (IOC) and test by using standard deviation and correlation of Cronbach. The qualitative analysis founds that ; To create the brand is highly important to run business, if business can create an acceptable from clients. It can create value added to products, by creating brand identity eg. Pattern, tailoring. Brand continuity and brand story, PR, build an image. Moreover, it is important for the companies to find the new market for their product to launch. The quantitative analysis found that ; Hermes Brand image from total effect analysis result from the Brand management Brand Value and identity Customer Trust and Strategic communication Statistically significant. Article history : Accepted 2 May 2015 SIMILARITY INDEX = 2.77